# Solve the differential equation y”-4y’+3y=f(t) with the initial conditions y(0) = 1 and y'(0) =-3 in the cases…

##### Home/Education/Expert Q&A/Solve the differential equation y”-4y’+3y=f(t) with the initial conditions y(0) = 1 and y'(0) =-3 in the cases…

**Question:**

Solve the differential equation y”-4y’+3y=f(t) with the initial conditions y(0) = 1 and y'(0) =-3 in the cases:

**(a)** f(t) = 0

**(b)** f(t) = 10e^{-2t}

**Click the button below to view answer!**

If you happen to run into some problem while following the steps, please make sure to let us know in the comment section below, and we’ll do our best to solve it. Apart from that, you can contact us on Facebook and Twitter, however we can’t guarantee a rapid reaction time over those platform

## 0 Comments